(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our research delineates novel subclasses of analytical functions using Euler polynomials. Afterwards, we estimate the Fekete -Szeg¨o functional problem and the Maclaurin coefficients for this subfamily, namely |a2| and |a3|. Additionally, several new results are shown to follow after specializing the parameters employed in our main results.